Effects of Husband Support, Family Income, Employed Mothers, and Antenatal Care Visit on Exclusive Breastfeeding - Widiantoro, Reza; Khairunnisa1, Khairunnisa; Furqon, Mashaf Fahrur Murdo; Murti, Bhisma; Handayani, Anggun Fitri (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Breastfeeding is advantageous to the infants health. Employed mothers experienced various challenges in providing exclusive breastfeeding. Studies suggest that husband support contribute to lactating mothers efficacy, improves breastfed duration, and reduces risk factors for bottle feeding. This study aimed to estimate the influence of husband's support, income, working mother, and ANC visits on exclusive breastfeeding. Subjects and Method: A systematic review and meta-analysis was conducted using PRISMA and PICO model. Population= lactating mothers. Intervention= low husband's support, high income, employed mother, irregular ANC visit. Comparison= high husband's support, low income, unemployed mother, regular ANC visits. Outcome= exclusive breastfeeding. Articles published from 2013 to 2023 were collected from Google Scholar, PubMed, and Science Direct. Literature search using the keywords